Konsumerisme, Etika Romantis, dan Kultus Diri: Telaah Ringkas Pemikiran Colin Campbell - Indra Setia Bakti; M Husen; Amiruddin Ketaren (Jurnal Sosiologi Agama Indonesia (JSAI), 2022)
Consumerism is a prevalent phenomenon that is already symptomatic in today's society. This study aims to discuss an ethic that supports the existence of a consumer society that was born and developed in a very long historical process. Colin Campbell was the first to speak of the romantic ethic that underlies the consumer society. This study uses the method of literature review. The main reference used is a book written by Campbell entitled "The Romantic Ethic and the Spirit of Modern Consumerism". The author also explores the essence of several other supporting books that provide interpretations and perspectives on Campbell's thoughts. The study results show several important concepts from Campbell's thought, including qualitative individualism, romantic ethics, and self-cult. These three conceptions are deeply attached to the spirit of humanism which became the catalyst for the Age of Enlightenment. Romantic ethical doctrine emphasizes the uniqueness or peculiarity of a person. Humans are encouraged to determine their destiny in developing themselves that are "genius, unique, and creative". As for consumption, it becomes a medium in the process of discovery and self-expression. Abstrak Konsumerisme telah menjadi fenomena yang menggejala di tengah kehidupan masyarakat dewasa ini. Studi ini membahas tentang sebuah etika yang mendukung eksistensi masyarakat konsumen yang lahir dan berkembang dalam proses sejarah yang sangat panjang. Colin Campbell pertama kali mengemukakan tentang etika romantis yang melandasi masyarakat konsumen. Studi ini menggunakan metode kajian pustaka. Referensi utama yang digunakan ialah buku yang ditulis oleh Campbell berjudul “The Romantic Ethic and the Spirit of Modern Consumerism”. Penulis juga menggali intisari dari beberapa buku pendukung lain yang memberikan penafsiran dan sudut pandang terhadap pemikiran Campbell. Hasil studi menampilkan beberapa konsep penting dari pemikiran Campbell, diantaranya individualisme kualitatif, etika romantis, dan kultus diri. Ketiga konsepsi tersebut sangat melekat dengan semangat humanisme yang menjadi katalis Abad Pencerahan. Doktrin etika romantis menekankan keunikan atau kekhasan seseorang. Manusia didorong menentukan nasib sendiri dalam mengembangkan dirinya yang “jenius, unik, dan kreatif”. Adapun konsumsi menjadi media dalam proses penemuan dan ekspresi diri.